Synthesis of Quinolino[1,2-c]quinazolin-6-one Derivatives via Formal (4+2)-Cycloaddition of Alkenes to Quinazolinе-Derived N-Acyliminium Cations: An Experimental and Theoretical Study - Filatov, Alexander S.; Larina, Anna G.; Petrov, Mikhail L.; Boitsov, Vitali M.; Stepakov, Alexander V. (Synthesis, 2022)
3-Aryl-4-hydroxy-1-methyl-3,4-dihydroquinazolin-2(1H)-ones were synthesized by reduction of 3-aryl-1-methylquinazoline-2,4(1H,3H)-diones with sodium triethylborohydride and studied as precursors of N-acyliminium cations that were expected to be trapped with various alkenes as (4+2)-cycloadducts. Unsubstituted 3-aryl-4-hydroxy-1-methyl-3,4-dihydroquinazolin-2(1H)-ones in the presence of BF3·Et2O failed to produce the desired cycloadducts probably due to a homooligomerization reaction involving N-acyliminium intermediates. To prevent this side reaction, we found it necessary to introduce substituents at both positions C6 and C8 of the quinazoline ring and C4′ of the 3-phenyl substituent. Utilizing bromine atoms as substituents at C6 and C8, N-acyliminium cations generated from 3-aryl-6,8-dibromo-4-hydroxy-1-methyl-3,4-dihydroquinazolin-2(1H)-ones in the presence of BF3·Et2O smoothly reacted with such alkenes as indene, acenaphthylene, styrene, α-methylstyrene to give new quinolino[1,2-c]quinazolin-6-one derivatives with high regio- and stereoselectivity. Density functional theory calculations were performed at the M06-2x/cc-pVDZ level to obtain an insight into the mechanism of the (4+2)-cycloaddition reaction of quinazoline-derived N-acyliminium cations to alkenes.
Keywords: stepwise cycloaddition; electrophilic addition; Friedel–Crafts alkylation reaction; N-acyliminium cations; electron-rich alkenes; regioselectivity; diastereoselectivity; DFT calculations